Organizational Strategies for Promoting Instructional Change: Implementation Dynamics in Schools Working With Comprehensive School Reform Providers - Rowan, Brian; Miller, Robert J. (American Educational Research Journal, 2007)
This article develops a conceptual framework for studying how three comprehensive school reform (CSR) programs organized schools for instructional change and how the distinctive strategies they pursued affected implementation outcomes. The conceptual model views the Accelerated Schools Project as using a system of cultural control to produce instructional change, the America's Choice program as using a model of professional control, and the Success for All program as using a model of procedural control. Predictable differences in patterns of organizing for instructional improvement emerged across schools working with these three programs, and these patterns were found to be systematically related to patterns of program implementation. In particular, the two CSR programs that were organized to produce instructional standardization produced higher levels of instructional change in the schools where they worked. The results of the study suggest organizational strategies program developers can use to obtain implementation fidelity in instructional change initiatives.
Keywords: Educational change; comprehensive school reform; implementation; instruction; school organization; school reform